2017
DOI: 10.1039/c6nr09321c
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-stripped naphthalocyanines for multimodal tumor theranostics with upconversion guidance cream

Abstract: Surfactant-stripped, nanoformulated naphthalocyanines (nanonaps) can be formed with Pluronic F127 and low temperature membrane processing, resulting in dispersed frozen micelles with extreme contrast in the near infrared. Here, we demonstrate that nanonaps can be used for multifunctional cancer theranostics. This includes lymphatic mapping and whole tumor photoacoustic imaging following intradermal or intravenous injection in rodents. Without further modification, pre-formed nanonaps were used for positron emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 62 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Such a combined CO and PTT therapy has been demonstrated to be more effective in destroying solid tumors than PB nanocube‐based PTT under the same NIR light irradiation condition . In another study, a 64 Cu‐labeled nanoformulated naphthalocyanines micelle was prepared and demonstrated as combined photoacoustic tomography and positron emission tomography guided NIR‐light‐activatable photothermal therapy reagent for treating 4T1 subcutaneous breast tumors in BALB/c mice . Upon NIR light (860 nm, 750 mW cm −2 , 3 min) irradiation, a delay growth of tumors was observed.…”
Section: Nir‐light‐initiated Nanomaterial‐mediated Photothermal Therapymentioning
confidence: 99%
“…Such a combined CO and PTT therapy has been demonstrated to be more effective in destroying solid tumors than PB nanocube‐based PTT under the same NIR light irradiation condition . In another study, a 64 Cu‐labeled nanoformulated naphthalocyanines micelle was prepared and demonstrated as combined photoacoustic tomography and positron emission tomography guided NIR‐light‐activatable photothermal therapy reagent for treating 4T1 subcutaneous breast tumors in BALB/c mice . Upon NIR light (860 nm, 750 mW cm −2 , 3 min) irradiation, a delay growth of tumors was observed.…”
Section: Nir‐light‐initiated Nanomaterial‐mediated Photothermal Therapymentioning
confidence: 99%
“…The macrocycle is well suited to form coordination complexes with various metals chelated in the center, which makes phthalocyanines and naphthalocyanines beneficial for optical imaging and phototherapy . However, the four phenyl groups or four naphthyl groups brings significant aggregation and solubility problems, therefore, phthalocyanines are usually modified with sulfonic acid groups or centrally coordinated metal atoms for better water solubility …”
Section: Current Organic Dyes For Nanomedicinementioning
confidence: 99%
“…Subsequently, the LDOS can be calculated according to Eq. (6). Across all calculations presented in this work, discretization steps of ∆k = 10 −3 and ∆ω = 10 −3 were used.…”
Section: Local Density Of Optical Statesmentioning
confidence: 99%
“…Upconversion (UC) is the process of converting two (or more) photons into one photon of higher energy. It is relevant in a broad range of applications, from anti counterfeiting [1,2], plastic recycling [3], bioimaging [4,5] and theranostics [5][6][7] to photovoltaics [8][9][10][11]. In photovoltaics, UC enables the utilization of sub-bandgap photons, which for silicon-based solar cells raises the theoretical efficiency limit from ≈ 30% [12] to ≈ 40% [8].…”
Section: Introductionmentioning
confidence: 99%